Introduction: Democracy Disorganized? - Jonathan Bach (Sociologica)
This article introduces three essays in the Focus section on “Problems of Democracy” adapted from the 25th Anniversary Conference of Columbia University’s Center on Organizational Innovation (COI). It argues that an ongoing shift in the organizational form of society from mass to network production and communication requires a new set of questions around the organization of democracy. Specifically, democracy’s core function of connecting power to accountability is shown through these essays to be increasingly dis-organized by this shift, necessitating new ways of addressing this old problem.